Chronic tibial pandiaphysitis with Brodie abscess due to Salmonella saprophyticus in a 29-year-old healthy man. (November 2016) - Durel, Cécile-Audrey; Ferry, Tristan; Vaz, Gualter; Perpoint, Thomas; Chidiac, Christian; Valour, Florent
Highlights: Osteomyelitis is a rare but classic complication of Salmonella infection. The Brodie abscess required a surgical osteotomy for excision of the infected bone tissue. Fluoroquinolone-based antimicrobial therapy for ≥6 weeks must be proposed. A longer duration may be required in the case of chronic infection with large lesions.